Upcycling : Decorate your house by giving new life to everyday objects. (Running Press Book Publishers, 2011)
Presents over one hundred projects for creative "upcycling"--using used and recycled products to create decorative items in the home, including leather belt doormats, bathroom towel picnic baskets, and a jar lid dining table --